1991
DOI: 10.1159/000186287
|View full text |Cite
|
Sign up to set email alerts
|

Renal Oncocytoma Developed in a Long-Term Hemodialysis Patient

Abstract: A case of renal oncocytoma which developed in a 38-year-old Japanese woman after 7 years of maintenance hemodialysis is reported. An encapsulated round tumor with a diameter of about 5 cm was incidentally discovered by abdominal echography. This is the first case of renal oncocytoma found in a long-term hemodialysis patient. Identification and differentiation of this subgroup from renal carcinomas are very important because of its benign nature. Careful clinicopathological investigation of renal tumors should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Unlike other solid masses, renal oncocytomas are rarely observed in dialysis patients with ACKD. A case presentation [5] describes the development of a renal oncocytoma in a 38-year-old patient following 7 years of hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other solid masses, renal oncocytomas are rarely observed in dialysis patients with ACKD. A case presentation [5] describes the development of a renal oncocytoma in a 38-year-old patient following 7 years of hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term dialysis patients with ACKD are 14 times more likely to develop renal adenocarcinoma than patients with end-stage renal disease without ACKD [4]. Renal oncocytomas, on the other hand, are rare in patients with ACKD [5][6][7]. Little has been published on the development of oncocytomas in the native kidneys of transplant recipients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Fur-ther studies needed to validate the results of this study. [8] Makita et al reported the first case of renal oncocytoma developed in a long-term hemodialysis patient, [11] however, no other reports could find an association between renal oncocytomas and end stage renal disease patients in hemodialysis.…”
Section: -Midlinementioning
confidence: 99%